1994
DOI: 10.1210/mend.8.5.8058071
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an up-stream promoter directing extrapituitary expression of the human prolactin gene.

Abstract: The human PRL gene is expressed outside pituitary lactotrophs in decidualized endometrium and lymphoid cells, but here the mRNA contains a 5'-untranslated region from an additional noncoding exon 1a. We have isolated a genomic DNA clone containing human PRL exon 1a with 2800 basepairs (bp) of 5'-flanking sequences. Sequencing locates exon 1a -5840 bp up-stream of the pituitary start site. To study its suspected regulatory function, various lengths of the 5'-flanking region were linked to the luciferase (Luc) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…The 5Ј-end of each of the deletion constructs was confirmed by sequencing. The human SERCA3 promoter-luciferase constructs and the unmodified, promoterless pGL3 basic reporter vector were used for transient transfection of the human cell line Jurkat E6.1 cells by electroporation as described (34). To evaluate transfection efficiencies, the cells were co-transfected with 150 or 500 ng of a pEL1-␀gal vector, containing the ␀-galactosidase reporter gene driven by the elongation factor 1 promoter (pEL1-␀gal vector is a gift from Dr. F. Bulens).…”
Section: Figmentioning
confidence: 99%
“…The 5Ј-end of each of the deletion constructs was confirmed by sequencing. The human SERCA3 promoter-luciferase constructs and the unmodified, promoterless pGL3 basic reporter vector were used for transient transfection of the human cell line Jurkat E6.1 cells by electroporation as described (34). To evaluate transfection efficiencies, the cells were co-transfected with 150 or 500 ng of a pEL1-␀gal vector, containing the ␀-galactosidase reporter gene driven by the elongation factor 1 promoter (pEL1-␀gal vector is a gift from Dr. F. Bulens).…”
Section: Figmentioning
confidence: 99%
“…Recent findings demonstrate that PRL production is not only restricted to the pituitary gland [40], which makes this theory interesting. In humans, there is a specific gene promoter allowing for PRL production in extra-pituitary locations [41], which implies that PRL not only functions as a regular hormone but potentially also as a local growth factor. Activation of the PRLR by PRL leads to activation of the JAK/STAT pathway [39,42].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of PRL, under control of the tissuespecific decidual PRL (dPRL) promoter (3,6), by ES cells coincides with decidual differentiation and is widely used as a biochemical marker of this process (2)(3)(4)(5)7). Previous studies have shown that CCAAT/enhancer-binding protein ␀ (C/ EBP␀), a member of the C/EBP subfamily of basic region/ leucine zipper transcription factors, is induced during ES cell differentiation (4).…”
mentioning
confidence: 99%